DALAM PERSPEKTIF EKONOMI, MUNGKINKAH REUNIFIKASI CHINA – TAIWAN DILAKUKAN MELALUI JALAN DAMAI - DIMASTI DANO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
The purpose of this study aims to analyze the influence of China-Taiwan economic relations, United States political relations, and Taiwan's internal factors on the peaceful reunification process. The research was conducted from 1 to 30 December 2022. Data collection techniques were through literature review related to research, including journals, news from social media, and others. In terms of economic perception, the opportunity for the peaceful reunification of China - Taiwan is still open, provided that the economic relations between the two countries can continue to be improved so that they become strong, integrated, and interdependent economic bonds. Learning from the Russia-Ukraine conflict, the military options taken by both sides will lead to the economic destruction